If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(3*x)/4 = 5*x+6/2 // - 5*x+6/2
(3*x)/4-(5*x)-(6/2) = 0
(3*x)/4-5*x-3 = 0
-17/4*x-3 = 0 // + 3
-17/4*x = 3 // : -17/4
x = 3/(-17/4)
x = -12/17
x = -12/17
| 5(y-2)+1=7y+8 | | (x^2+4x)=0 | | 3(4-5)=52 | | -6(0.1x+0.5)-1.1=-0.5 | | 70=2(15)+2(x+12) | | 7x+9y=3 | | 3+5(2-x)=2(x+4) | | y=19.66666667-7 | | 3-4x=111 | | 9x^2-12x=-5 | | -(1-3x)+4x=-15 | | (14x^2+6x+10)-(2x^2+8)= | | -8(-2m-8)+1=-31+4m | | y=.4x+1.2 | | -5x=-63+2x | | W=F(r+A) | | 1/3x=14 | | 26=5x+10+3x | | y=3+2*3 | | y=3+2*2 | | x/3=-20 | | 3(x+9)=4x-13 | | y=3+2*1 | | y=3+2*0 | | y=3+2*-1 | | y=3+2*-2 | | 4(-1)+y=-7 | | y=2+2*3 | | -22=d/17 | | y=2+2*2 | | 4(5+x)=5(4x-1)-23 | | y=2+2*1 |